2020
DOI: 10.13106/jafeb.2020.vol7.no9.293
|View full text |Cite
|
Sign up to set email alerts
|

Does Fixed Assets Revaluation Create Avenues for Financial Numbers Game? Evidence from a Developing Country

Abstract: The study reveals the extent of changes in selective financial numbers caused by fixed asset revaluation (FAR) and explores whether there was a management motive for playing the financial numbers game through using the FAR model. The data set consists of a sample of 142 listed companies purposively selected from 13 industries. The study found a significant impact of FAR on the net asset value (NAV), fixed asset intensity (FAI), and debt-to-equity ratio (DER). These findings are supported by the political cost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The application of the FAR model as an accounting policy choice has been a topic of long-standing debate among academics, investors, corporate managers, standard setters, and regulators (Christensen and Nikolaev, 2013;Rahman and Hossain, 2020). Therefore, empirical research on asset revaluation has been undertaken in many developed and developing countries covering the issues, such as the motivation behind FAR, factors influencing FAR, the timing of revaluation, the effects of FAR on future firm performance, and so forth.…”
Section: Review Of Literaturementioning
confidence: 99%
See 4 more Smart Citations
“…The application of the FAR model as an accounting policy choice has been a topic of long-standing debate among academics, investors, corporate managers, standard setters, and regulators (Christensen and Nikolaev, 2013;Rahman and Hossain, 2020). Therefore, empirical research on asset revaluation has been undertaken in many developed and developing countries covering the issues, such as the motivation behind FAR, factors influencing FAR, the timing of revaluation, the effects of FAR on future firm performance, and so forth.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The paper has emphasized the honesty of management behind the FAR decision. The study of Rahman and Hossain (2020) observed that FAR has a significant effect on the net asset value (NAV), FAI, and DER of companies in the subsequent year of revaluation. The study also found an increase of 427% in NAV and a decrease of 70% in DER originated essentially by FAR.…”
Section: Far Future Firm Performance and Market Reactionmentioning
confidence: 99%
See 3 more Smart Citations